Development of Emotional Well-Being indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2019) - Hitzig, Sander L.; Titman, Rebecca; Orenczuk, Steven; Clarke, Teren; Flett, Heather; Noonan, Vanessa K.; Bain, Patricia; Mills, Sandra; Farahani, Farnoosh; Wiest, Matheus Joner; Jeyathevan, Gaya; Alavinia, S. Mohammad; et al.
Abstract : Context: Emotional Well-Being (EWB) post-spinal cord injury or disease (SCI/D) is a critical aspect of adjustment to disability. Advancing care and assuring equity in care delivery within this rehabilitation care domain is essential. Herein, we describe the selection of EWB structure, process and outcome indicators for adults with SCI/D in the first 18 months after rehabilitation admission. Methods: A pan-Canadian Working Group completed the following tasks: (1) defined the EWB construct; (2) conducted a systematic review of available outcomes and their psychometric properties; (3) constructed a Driver diagram summarizing available evidence associated with EWB; and, (4) prepared a process map. Facilitated meetings allowed selection and review of feedback following rapid-cycle evaluations of proposed structure, process and outcome indicators. Results: The structure indicator is the proportion of staff with appropriate education and training in EWB and access to experts and resources. The process indicator is the proportion of SCI/D patients who were screened for depression and anxiety symptoms at rehabilitation admission and rehabilitation discharge. The intermediary outcome is the proportion of SCI/D patients at risk for depression or anxiety at rehabilitation discharge based on screening symptom scores. The final outcomes are: (a) proportion of individuals at risk for depression or anxiety based on screening symptom scores; and (b) proportion of individuals who received referral for EWB services or intervention. Conclusion: The proposed indicators have a low administrative burden and will ensure feasibility of screening for depression and anxiety at important transition points for individuals with SCI/D. We anticipate that the current structures have inadequate resources for at-risk individuals identified during the screening process.